P149 Designing a management plan: a mixed methods approach to exploring patient journeys in children with severe and recurrent wheeze. (15th November 2016) - Naidu, SB; Kerr, R; Kecman, M; Klaber, R
Abstract : Introduction: Management plans, while recommended nationally to reduce burden of asthma on individuals and healthcare systems, are poorly and infrequently used (BTS/SIGN 2014). Studies show a mismatch between patients' expectations and what professionals provide. (Ring et al, 2011). Aim: An exploration of health journeys of children with severe and recurrent wheeze: what makes a good management plan? Methods: Purposeful sampling techniques were used to recruit patients. A convergent mixed-methods design, comprised of semi-structured interviews and notes review, was used. Data was analysed using inductive thematic analysis and descriptive statistics. Results: Eleven children were recruited. Parents are motivated by symptoms and their own perceptions of wheeze to take action. They seek advice from multiple sources according to their own preferences, rather than symptom severity. The median number of admissions to A and E in the last two years was 3, and of GP consultations was 6.5; there was a negative correlation between these. Barriers to self-management include lack of knowledge, confidence and appropriate resources. Notably, healthcare professionals influenced the ability and willingness to self-manage by either empowering patients or providing paternalistic instruction. There was occasionally poor communication of agreed actions between primary and secondary care, which confused patients. Not all A and E attendances were noted in the GP system, and only one of 5 requests for GP follow-up was carried out. It was noted that patients see A and E as 'specialist' and may not follow-up with a 'general' physician upon discharge. Parents and children saw management plans as able to address key barriers. However, no notes in both GP and A and E mentioned providing a written plan. Conclusion: Our data suggests the need to 'nudge' parents to self-manage before escalating appropriately by modifying existing management plans. Plans should be personalised, for example to target management of key triggers. Crucially, patients and both primary and secondary healthcare professionals must work together to implement mutually acceptable plans. We are using our data to create a mobile-based application which can be integrated into primary and secondary care, and is responsive to patients' desires. Preliminary results show this will be well-received, and is perceived to be superior to paper-based plans.